Pengolahan Limbah Cair Tahu Menjadi Pupuk Organik Cair (POC) untuk Pertanian Berkelanjutan Desa Kunir Kidul Kabupaten Lumajang: Processing of Liquid Tofu Waste into Liquid Organic Fertilizer (LOF) for Sustainable Agriculture in Kunir Kidul Village, Lumajang Regency - Ria Dewi Andriani; Yuli Frita Nuningtyas; Jaisy Aghniarahim Putritamara; Nimas Mayang Sabrina Sunyoto; Rischa Amalia Saleha (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The tofu industry is one of the soybean-based food processing sectors that generates liquid waste with high organic content. Kunir Kidul Village in Lumajang Regency is one of the centers of small-scale household tofu production, where most producers still lack adequate waste management systems. This community service program aims to improve local residents’ knowledge and skills in processing tofu wastewater into liquid organic fertilizer through fermentation with effective microorganisms (EM). The activities were carried out through stages of socialization, training, mentoring, and evaluation, involving tofu MSME owners and local farmer groups. Liquid organic fertilizer was produced by mixing tofu wastewater, molasses, EM-4, rice-washing water, and additional organic materials, then fermenting for 14–15 days using an airlock system. The fermentation process produced a dark-brown liquid fertilizer with a fresh aroma and a pH of 4.5–6.5. The resulting product can be applied to plants by soil drenching or foliar spraying and has been proven to enhance the vegetative growth of chili and mustard plants. This activity not only reduces the potential for environmental pollution but also creates new business opportunities based on a circular economy model, supporting the implementation of sustainable agriculture and the Sustainable Development Goals (SDGs) at the village level. Furthermore, the program contributes to achieving the SDGs, particularly SDG 2 through increased agricultural productivity, SDG 6 through reduced liquid waste pollution, SDG 8 through the creation of new economic opportunities, SDG 12 through the implementation of circular economy practices, and SDG 13 through reduced dependence on chemical fertilizers.